KOHESI SOSIAL DAN KEBERAGAMAN AGAMA: STUDI PERBANDINGAN MODAL SOSIAL SUNDA WIWITAN KUNINGAN DAN CIMAHI, JAWA BARAT - Mahmudin Mahmudin; Edi Junaedi; Husni Mubarok; Dedi Slamet Riyadi (Penamas, 2021)
In the last two decades Indonesia has been faced to the problem of inclining the tendency of intolerance, both at the level of perception and action. Viewed from several cases, many acts of intolerance are experienced by minorities, especially religious and religious ethnic minorities. The study analyzes how social capital works in the establishment of social cohesion of minority belief groups Sunda Wiwitan (SW) at two different regions, i.e. Cigugur, Kuningan and Cireundeu, Cimahi, both are in West Java. The study uses qualitative research method. The data collected through interview techniques, secondary data analysis, and observation. The study found that although the two different SW Communities shared same teachings, they showed different character of social cohesion. Social cohesion in Kuningan is more vulnerable to be concerned by other parties than in Cireundeu, Cimahi.